Distribution and Source of Sedimentary Polycyclic Aromatic Hydrocarbon (PAHs) in River Sediment of Jakarta - Rinawati Rinawati; Hideshige Takada (Universitas Gadjah Mada, 2017)
In this study, the distribution and source identification of sedimentary PAHs from 13 rivers running through Jakarta City were investigated. Freeze-dried sediment samples were extracted by pressurized fluid extraction and purified by two-step of column chromatography. PAHs were identified and quantified by gas chromatography-mass spectrometry (GC-MS). High concentrations of PAHs, ranging from 1992 to 17635 ng/g-dw, were observed at all sampling locations. Ratios of alkylated PAHs to parent PAHs exhibited both petrogenic and pyrogenic signatures with predominantly petrogenic inputs. High hopanne concentrations (4238-40375 ng/g dry sediment) supported the petrogenic input to Jakarta’s rivers. The high concentration of PAHs is indicator for organic micropollutant in the aquatic urban environment in Jakarta that may have the potential to cause adverse effect to the environment.